2023
DOI: 10.3389/fanim.2022.998012
|View full text |Cite
|
Sign up to set email alerts
|

Performance of food–feed maize and cowpea cultivars under monoculture and intercropping systems: Grain yield, fodder biomass, and nutritive value

Abstract: Livestock feeding in Burkina Faso is characterized by a recurrent deficit in both the quality and the quantity of fodder during the dry season, which affects animal performance. To overcome this, quality fodder/forage production is an alternative. Therefore, this study evaluated food- and feed-improved cultivars of maize and cowpea in intercropping trials using the “mother and baby trials” approach with crop–livestock farmers. The mother trial comprised a randomized block design with eight treatments and four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Also, this dual-purposes cropping system improves soil fertility and helps control weeds and climatic hazards (Konlan et al, 2018). The groundnut-corn cropping association constitute a key to strengthening the resilience of smallscale dairy farmers to climate variability and the adverse impacts of environmental conditions (Sanfo et al, 2023). In West Africa, several studies have allowed the selection of improved dual-purpose varieties of graminaceous and leguminous plants with good fodder and grain performance (Sanginga et al, 2003;Hassan et al, 2015 ;Ouattara et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Also, this dual-purposes cropping system improves soil fertility and helps control weeds and climatic hazards (Konlan et al, 2018). The groundnut-corn cropping association constitute a key to strengthening the resilience of smallscale dairy farmers to climate variability and the adverse impacts of environmental conditions (Sanfo et al, 2023). In West Africa, several studies have allowed the selection of improved dual-purpose varieties of graminaceous and leguminous plants with good fodder and grain performance (Sanginga et al, 2003;Hassan et al, 2015 ;Ouattara et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Cereal and legume intercropping is more suitable for agropastoralists and sedentary crop-livestock farmers because of this dual need for food and feed for human beings and livestock, respectively (Nasir et al, 2019). The use of improved food-feed cultivars, which can fit into smallholder farmer's cropping calendar, is likely to provide greater benefits both for grains and fodder biomass (Mbaye et al, 2014;Louarn et al, 2016;Abera et al, 2021;Sanfo et al, 2023). Previous studies revealed that intercrop of maize-cowpea-sorghum-cowpea led to an increase in grain yield and fodder biomass in the range of 30-60% with better weed control (Matusso et al, 2014;Obulbiga et al, 2015;Coulibaly et al, 2017;Sanfo et al, 2023), and land equivalent rations were greater in cowpea-maize intercropping systems (Sanfo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The use of improved food-feed cultivars, which can fit into smallholder farmer's cropping calendar, is likely to provide greater benefits both for grains and fodder biomass (Mbaye et al, 2014;Louarn et al, 2016;Abera et al, 2021;Sanfo et al, 2023). Previous studies revealed that intercrop of maize-cowpea-sorghum-cowpea led to an increase in grain yield and fodder biomass in the range of 30-60% with better weed control (Matusso et al, 2014;Obulbiga et al, 2015;Coulibaly et al, 2017;Sanfo et al, 2023), and land equivalent rations were greater in cowpea-maize intercropping systems (Sanfo et al, 2023). Considering the multiple benefits of using improved cultivars and appropriate cropping systems, we hypothesized that intercropping of best-bet sorghum and cowpea cultivars will provide greater grain yield and fodder biomass as well as quality fodder in smallholder farming systems in Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%